Climate Smart Advisories - Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ethiopia Digital Agricultural Extension and Advisory Services (DAEAS ) Roadmap National Convening. Adama, Ethiopia April 11-13, 2022.